Evaluation of the anti-diarrheal effects of the whole plant extracts of Cuscuta reflexa Roxb in pigeons. (2021) - Muhammad, Naveed; Ullah, Sana; Rauf, Abdur; Atif, Muhammad; Patel, Seema; Israr, Muhammad; Akbar, Sajid; Shehzad, Omer; Saeed, Muhammad; Bawazeer, Saud; Uddin, Md. Sahab; Derkho, Marina; et al.
Graphical abstract: Highlights: The antidiarrheal activity of C. reflexa was evaluated in pigeons using the juice, aqueous, and methanol extracts. The antidiarrheal effect of C. reflexa was evaluated using different reported research models. The juice, aqueous, and methanol extract of C. reflexa exhibit significant anti-motility and anti-secretory potential. Abstract: Background: Cuscuta reflexa (dodder) belonging to the family Convolvulaceae has many ethno-medicinal uses such as antidiarrheal and antiemetic. This plant has been employed to treat diarrhea, where the antidiarrheal use of this plant is well established in different communities around the world without scientific bases. In addition, the antibacterial, anthelmintic, anticholinergic, and antihistaminic effects of this parasitic vine are partly responsible for the folkloric antidiarrheal use of this plant. In the present study, the antidiarrheal activity of C. reflexa was evaluated in pigeons ( Columba livia ) using the juice (JCR), aqueous (CRAE), and methanol (CRME) extracts. Methods: The antidiarrheal effect of C. reflexa was evaluated using different reported research models, with few modifications. In pigeons, diarrhea was induced by administration of castor oil (6 mL/kg, PO), ampicillin (250 mg/kg, IP), magnesium sulfate (2 gm/kg, PO), and cisplatin (6 mg/kg, IV). In these experiments, loperamide (2 mg/kg, IM) was used as a positive control, whereas JCR (1 mL/kg (1%) and 1 mL/kg (2%), CRAE (50, 100 and 200 mg/kg) and CRME (50, 100 and 200 mg/kg) were administered intramuscularly at different doses into each pigeon in the test groups. Results: In addition to cisplatin-induced diarrhea, all paradigms tested gave significant results ( P < 0.01). The JCR, at different doses, exhibited a significant ( p < 0.01) a dose-dependent antidiarrheal effect on both the frequency and the onset of diarrhea. Similarly, CRAE and CRME, at doses of 100 and 200 mg/kg, showed considerable ( p < 0.001) inhibition against the onset and frequency of diarrhea. On the other hand, JCR, CRAE, and CRME exerted significant effects ( p < 0.001) on the percentage inhibition (PI) of diarrhea and gastrointestinal charcoal transit in a dose-dependent manner. In this respect, the maximum PI ( p < 0.01) of JCR, CRAE, and CRME in different experimental paradigms was 43.13, 49.14, and 55.99 %, respectively. Conclusions: Taken all together, results from this study reveal that the juice, aqueous, and methanol extract of C. reflexa exhibit significant anti-motility and anti-secretory potential. These findings may explain the medicinal use of C. reflexa in folk medicine as an antidiarrheal medicinal plant.